Segmentation in interrogative utterances (on the material of contemporary French fiction) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
This article is devoted to the analysis of main characteristics of interrogative segmented utterances that present a synthesis of segmented structure and interrogative sentence. This type of utterance has a certain syntactic structure that conditions its semantic and pragmatic characteristics.
Keywords: segmentation; interrogative segmented utterance; detached component; topic (theme)